-12.7+-4.4=x

Simple and best practice solution for -12.7+-4.4=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12.7+-4.4=x equation:


Simplifying
-12.7 + -4.4 = x

Combine like terms: -12.7 + -4.4 = -17.1
-17.1 = x

Solving
-17.1 = x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-17.1 + -1x = x + -1x

Combine like terms: x + -1x = 0
-17.1 + -1x = 0

Add '17.1' to each side of the equation.
-17.1 + 17.1 + -1x = 0 + 17.1

Combine like terms: -17.1 + 17.1 = 0.0
0.0 + -1x = 0 + 17.1
-1x = 0 + 17.1

Combine like terms: 0 + 17.1 = 17.1
-1x = 17.1

Divide each side by '-1'.
x = -17.1

Simplifying
x = -17.1

See similar equations:

| K+(-6)=4 | | -3x-3+9x+7-x=29 | | -3x-3+9x+7x-x=29 | | (6x-w)(7x+w)= | | 14z+11-5z= | | 2+(-9)=f-4 | | 2mp+3np+2mr+3nr= | | 3n-4+6n+2=6+4n+2 | | (-5)-(-8)=g+7 | | 4x+4=19-x | | (-37)=c+(-14) | | 6a-2-4a=3a+4+5a | | 0=-5n-2n-2n | | (-5)=b+(-11) | | -8x^2-8x+160=0 | | A-5=(-8) | | 3x*26= | | 6(x-1)+2=6x-2 | | -7y=-10-8y | | 0=-4.9t^2+.686t | | J+(-3)=4 | | 7j+4=5j | | -5x-15=-20 | | 9y=9+10y | | -12+8+5=36 | | 2x+34x^2-322=0 | | 3+(-7)=f-3 | | 3y+9-8y+6-6=-5y-12 | | -12+3x=-6 | | 9n=-117 | | 3x+9-8x+6-6=-5x-12 | | 3+(-7)=4 |

Equations solver categories